The Meaning Of Happiness In The Royal Court Community Of Yogyakarta - Ripai, Ganjar Ahmad; Nurhayati, Siti Rohmah (International Journal Labs, 2024)
The concept of happiness is an important process for every living being. Happiness is when someone feels satisfied with what they do, feels happy when they are with someone, and they are happy when they get praise. This research is to find out the meaning of happiness of the Yogyakarta Palace's Abdi Dalem Community. The purpose of this study was to determine the description of the happiness of the indigenous people of the Yogyakarta palace. This research uses a qualitative research method with a phenomenological approach conducted in the Yogyakarta palace from September to November 2023. Information was obtained using interview techniques with subjects who served the Yogyakarta palace. The data analysis carried out in this study is a qualitative data analysis in which the data analyzed is all the data encountered in the field, used miles and Huberman interactive data by carrying out data reduction. then proceed with the presentation of data and end with drawing conclusions on the results of the research that has been carried out.